Confirmatory Factor Analysis of the Enriched Life Scale Among US Military Veterans - Angel, Caroline M. (Front Psychol, 2019)
The Enriched Life Scale (ELS) is a 40-item measure developed by the military veteran service organization, Team Red, White & Blue (RWB), to systematically capture and quantify the lived experiences of military veterans transitioning to civilian life. As Team RWB’s mission is to “enrich veterans’ lives,” veterans who conceived of and co-developed the ELS as a psychometric instrument defined what an “enriched life” would entail. Exploratory factor analysis (EFA) of the ELS revealed a five-factor structure capturing the domains of: physical health, mental health, genuine relationships, sense of purpose, and engaged citizenship. The goal of the current study was to use confirmatory factor analysis to validate the factor structure of the ELS in a sample of veterans not affiliated with Team RWB. We also sought to explore convergent validity with the Military to Civilian Questionnaire, a measure of military to civilian reintegration challenges. Five hundred and twenty-nine veterans participated in the study. We estimated three models, one-factor, four-factor, and five-factor model via maximum likelihood estimation with robust Huber-White standard errors. The five-factor model showed the best fit to the data (RMSEA = 0.05, CFI = 0.90, TLI = 0.90, SRMR = 0.06). Additionally, the five-factor model demonstrated convergent and discriminant validity, as well as internal consistency reliability (genuine relationships, α = 0.90; sense of purpose, α = 0.93; engaged citizenship, α = 0.89; mental health, α = 0.88; and physical health, α = 0.78). Overall, the ELS is a valid and reliable measure of veteran enrichment and could potentially be used in conjunction with diagnostic instruments that capture strain-related transition challenges (to include mental health disorders) to capture post-military service wellbeing.